Cover JAA Vol. 7, No. 4, Oktober 2018 - JAA, Pengelola (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.4, Oktober 2018, 2018)
Cover JAA Vol. 7, No. 4, Oktober 2018